Performa Tungku Hibrid Energi Surya dan Gas untuk Alat Pengering Kabinet dengan Sistem Cerdas - Indonesia Indonesia; Mursalim Mursalim; Anugerah Fitri Amalia (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
This study aims to evaluate the performance of a cabinet dryer that uses hybrid solar energy and LPG. Renewable energy is essential for agricultural drying. This hybrid system dryer uses fuzzy logic and expert system technology to optimize the amount of energy used. The test methods include tests of solar collectors, air and gas valves, and drying and energy consumption using 10 kg of fresh sago. The results show that hybrid and non-hybrid (gas only) fulfill sago's temperature and moisture content requirements for drying. With the integration of fuzzy logic and expert system technology, the machine can optimize solar and gas energy efficiency, resulting in 53% out of 100% savings compared to non-hybrid. In addition to energy savings, the operating cost of the hybrid system is cheaper than non-hybrid. In conclusion, applying a solar-LPG hybrid system in a cabinet-type dryer can optimize performance and reduce energy consumption and operating costs.